Labor Market Slack in the EU during the COVID–19 Crisis - Rollnik‑Sadowska, Ewa; Cichowicz, Ewa; Dębkowska, Katarzyna (Comparative Economic Research. Central and Eastern Europe, 2024)
The general aim of the article is to verify the extent of labor market slack at three moments considered crucial when analyzing labor market changes caused by the COVID–19 pandemic. The main goal is to identify similarities and differences between EU countries grouped into clusters identified during the research. The study uses cluster analysis to classify the EU members into groups of similar countries according to the labor market slack variables observed before (2019) and during the pandemic (2020, 2021). A two‑stage approach was selected. In the first stage, hierarchical analysis was used to determine the initial number of groups, while in the second stage, the proper classification of objects was made using the k‑means method. A comparison of changes taking place in the labor markets of the analyzed countries allows us to select four homogeneous clusters of countries in all periods under study. The results also show that the labor market slack in most EU countries did not change over the analyzed period, although some countries improved (like Ireland, France, and Cyprus). The reason could be the effectiveness of measures that support labor markets that were implemented during the pandemic. The country where the labor market slack situation worsened is Italy. It would be valuable to analyze in more detail the effectiveness of labor market policies and programs from countries in the identified clusters because they contributed to a relatively stable labor market slack situation. Future research should also be directed towards analyzing changes on the side of employment, including a sectoral analysis, which would expand the knowledge of the labor market during the COVID–19 crisis. Moreover, to deepen the analysis of labor market slack, the demographic structure could be included. Analysis of the labor market based solely on the unemployment rate is insufficient, which is even more visible in the face of the consequences caused by the COVID–19 pandemic as that measure does not include the “discouraged worker effect”. For the EU, there is a research gap regarding this effect, which can be gleaned from the labor market slack statistics. This article, therefore, fills the gap.